Pembelajaran Pendidikan Agama Islam Berbasis Moderasi Beragama Menuju Society Era 5.0 - Shofyan, Ahmad (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2022)
Religious moderation is the most perfect action in dealing with problems in various local regions that have a diversity of religions. Whereas the learning of Islam seeks to provide the provision of religious knowledge to students so that they have the will to learn to believe and fear Allah SWT. The results of the field investigation that had been carried out previously show that PAI learning has not been integrated with emphasis on the social education process. But to form students who are pious individually (habl min Allah), but not horizontally socially (habl min nas). And also PAI learning is only oriented to the basic concepts of Islamic teachings. The method used in writing this article is the library method. Reviewing the components of Islamic religious education learning based on religious moderation in terms of curriculum, educators, materials, media and methods, evaluation. The purpose of the study is to build good and directed communication that Islamic religious education is based on religious moderation towards Society 5.0 is a way to continue to build a sense of tolerance and moderation. For this achievement, there are big challenges in building young people who think globally and behave locally as research targets, namely by forming responsibility, respecting differences, collaborating with mutual distance, building goodness and communication.